Optical glass, optical components and optical instruments

By designing optical glass with a refractive index of 1.45~1.51 and an ABE number of 66~74, the problem of oxidation and erosion of the mold in high temperature environment is solved, low transition temperature and high UV radiation resistance are achieved, and it is suitable for precision molding.

CN117285250BActive Publication Date: 2025-03-25CDGM OPTICAL GLASS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311239649.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

When existing optical glass is used in high temperature environments, the mold is easily oxidized and eroded, resulting in a shortening of the mold life and its high transition temperature is not conducive to precision molding.

Method used

An optical glass with a refractive index of 1.45 to 1.51 and an Abbe number of 66 to 74 was designed, and its composition includes SiO2, B2O3, K2O and F. Through reasonable component proportion optimization, the transition temperature and density of the glass are reduced.

Benefits of technology

It achieves the high UV radiation resistance and excellent optical properties of optical glass while maintaining low transition temperature and low density, extending the service life of the mold and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004466778150000141
    Figure BDA0004466778150000141
  • Figure BDA0004466778150000161
    Figure BDA0004466778150000161
  • Figure BDA0004466778150000171
    Figure BDA0004466778150000171
Patent Text Reader

Abstract

The present invention provides an optical glass, the components of which are expressed in weight percentage and contain: SiO2: 50-70%; B2O3: 2-18%; K2O: 10-30%; F: greater than 3% but less than or equal to 20%, wherein SiO2 / (K2O+F) is 1.2-4.5. Through reasonable component design, the optical glass of the present invention has a desired refractive index and Abbe number, as well as a relatively low transition temperature and density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical glass, in particular to an optical glass with a refractive index of 1.45-1.51 and an Abbe number of 66-74, and an optical element and an optical instrument made of the optical glass. Background Art

[0002] In recent years, with the development of optoelectronic information, digital display and other fields, the requirements for miniaturization, lightweight and high performance have been put forward for optical components used in optical systems. At present, the mainstream manufacturing method of optical components is precision molding, including direct molding and secondary molding, which can reduce the consumption of raw materials, reduce manpower and material costs, and reduce environmental pollution. This technology can produce aspheric components in large quantities at low cost. The so-called precision molding is to mold glass preforms with high-precision molds with a predetermined product shape under a certain temperature and pressure, so as to obtain glass products with the final product shape and optical functions. Various optical components such as spherical lenses, aspheric lenses, prisms and diffraction gratings can be manufactured through precision molding technology.

[0003] When precision molding is performed, in order to replicate the high-precision mold surface on the finished glass product, it is necessary to pressurize the glass preform at high temperature (usually above the glass transition temperature of 20 to 60°C). At this time, the molding mold is under high temperature and pressure, and the mold surface is easily oxidized and corroded even in a protective gas. In order to extend the life of the mold and inhibit the damage to the mold by the high temperature environment, the molding temperature must be reduced. Therefore, the transition temperature of the optical glass used for molding needs to be as low as possible. Chinese patent CN101300202A discloses an optical glass with a refractive index of 1.45 to 1.65 and an Abbe number of 65 or more, and its transition temperature needs to be further reduced. Chinese patent CN108529874A discloses an optical glass with a refractive index of 1.42 to 1.53 and an Abbe number of 55 to 98. Although its transition temperature is low, its density is relatively high, which is not conducive to the requirement of lightweight. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an optical glass with a refractive index of 1.45-1.51 and an Abbe number of 66-74.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] (1) Optical glass, the components of which, expressed in weight percentage, contain: SiO2: 50-70%; B2O3: 2-18%; K2O: 10-30%; F: greater than 3% but less than or equal to 20%, wherein SiO2 / (K2O+F) is 1.2-4.5.

[0007] (2) The optical glass according to (1), wherein the components, expressed in weight percentage, further contain: Al2O3: 0-5%; and / or Nb2O5: 0-2%; and / or TiO2: 0-2%; and / or ZrO2: 0-3%; and / or Na2O: 0-7%; and / or Li2O: 0-5%; and / or Ln2O3: 0-5%; and / or WO3: 0-2%; and / or Ta2O5: 0-3%; and / or Or Bi2O3: 0-2%; and / or RO: 0-8%; and / or ZnO: 0-5%; and / or P2O5: 0-3%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, RO is one or more of BaO, SrO, CaO, and MgO, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

[0008] (3) Optical glass, comprising SiO2, B2O3, K2O and F, wherein the composition is expressed in weight percentage, wherein SiO2 / (K2O+F) is 1.2 to 4.5, and the refractive index of the optical glass is n d is 1.45~1.51, Abbe number v d 66~74, transition temperature T g The temperature is below 490℃ and the density is 2.70g / cm 3 the following.

[0009] (4) The optical glass according to (3), wherein the components, expressed in weight percentage, are: SiO2: 50-70%; and / or B2O3: 2-18%; and / or K2O: 10-30%; and / or Nb2O5: 0-2%; and / or TiO2: 0-2%; and / or ZrO2: 0-3%; and / or F: greater than 3% but less than or equal to 20%; and / or Al2O3: 0-5%; and / or Na2O: 0-7%; and / or Li2O: 0-5%; and / or Ln2O3: 0-1 ... Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2%; and / or Nb2O5: 0-2% 5%; and / or WO3: 0-2%; and / or Ta2O5: 0-3%; and / or Bi2O3: 0-2%; and / or RO: 0-8%; and / or ZnO: 0-5%; and / or P2O5: 0-3%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, RO is one or more of BaO, SrO, CaO, and MgO, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

[0010] (5) The optical glass according to any one of (1) to (4), wherein the components thereof, expressed in weight percentage, satisfy one or more of the following five conditions:

[0011] 1) F / B2O3 is 0.2 to 5.0, preferably F / B2O3 is 0.3 to 2.0, more preferably F / B2O3 is 0.4 to 1.5, and further preferably F / B2O3 is 0.5 to 0.9;

[0012] 2) Al2O3 / F is less than 1.0, preferably Al2O3 / F is less than 0.8, more preferably Al2O3 / F is 0.01 to 0.5, and further preferably Al2O3 / F is 0.07 to 0.3;

[0013] 3) K2O / F is 0.7 to 7.0, preferably K2O / F is 1.0 to 5.0, more preferably K2O / F is 1.5 to 3.0, and further preferably K2O / F is 1.8 to 2.8;

[0014] 4) SiO2 / (K2O+F) is 1.3 to 3.5, preferably SiO2 / (K2O+F) is 1.5 to 3.0, and more preferably SiO2 / (K2O+F) is 1.7 to 2.5;

[0015] 5) (ZrO2+Nb2O5+TiO2) / F is 0.01~1.0, preferably (ZrO2+Nb2O5+TiO2) / F is 0.01~0.8, more preferably (ZrO2+Nb2O5+TiO2) / F is 0.02~0.6, and further preferably (ZrO2+Nb2O5+TiO2) / F is 0.03~0.4.

[0016] (6) The optical glass according to any one of (1) to (4), wherein the composition is expressed in weight percentage, wherein: (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is greater than 0 but less than or equal to 0.8, preferably (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01 to 0.5, and more preferably (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01 to 0.5. a2O5+WO3) / B2O3 is 0.01 to 0.3, and more preferably (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.02 to 0.2; and / or (Nb2O5+TiO2) / Al2O3 is 2.0 or less, and preferably (Nb2O5+TiO2) / Al2O3 is 0.01 to 1.5, and more preferably (Nb2O5+TiO2) / Al2O3 is is 0.05 to 1.0, and more preferably (Nb2O5 + TiO2) / Al2O3 is 0.1 to 0.5; and / or (Li2O + Na2O + K2O) / B2O3 is 0.7 to 6.0, and preferably (Li2O + Na2O + K2O) / B2O3 is 0.8 to 5.0, and more preferably (Li2O + Na2O + K2O) / B2O3 is 1.0 to 3.0, and more preferably (Li2O + Na2O + K2O) / B2O3 is 1.0 to 3.0. O+K2O) / B2O3 is 1.5~2.0; and / or (Li2O+Na2O+K2O) / SiO2 is 0.15~0.8, preferably (Li2O+Na2O+K2O) / SiO2 is 0.18~0.7, more preferably (Li2O+Na2O+K2O) / SiO2 is 0.2~0.6, and further preferably (Li2O+Na2O+K2O) / SiO2 is 0.2~0.45.

[0017] (7) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: SiO2: 52-68%, preferably SiO2: 54-64%; and / or B2O3: 4-16%, preferably B2O3: 8-14%; and / or K2O: 12-27%, preferably K2O: 13-25%; and / or Nb2O5: 0-1%, preferably Nb2O5: 0-0.8%; and / or or TiO2: 0-1%, preferably TiO2: 0-0.8%; and / or ZrO2: 0-2%, preferably ZrO2: 0-1%; and / or F: 5-16%, preferably F: 6-12%; and / or Al2O3: 0.1-3%, preferably Al2O3: 0.2-2%; and / or Na2O: 0-5%, preferably Na2O: 0-3%; and / or Li2O: 0-4%, preferably Li2O: 0- 3%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%; and / or WO3: 0-1%, preferably WO3: 0-0.5%; and / or Ta2O5: 0-2%, preferably Ta2O5: 0-1%; and / or Bi2O3: 0-1%, preferably Bi2O3: 0-0.5%; and / or RO: 0-5%, preferably RO: 0-2%; and / or ZnO: 0-2%, preferably ZnO : less than 1%; and / or P2O5: 0-2%, preferably P2O5: 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, RO is one or more of BaO, SrO, CaO, MgO, and the clarifier is one or more of Sb2O3, SnO2, CeO2.

[0018] (8) The optical glass according to any one of (1) to (4), which does not contain Na2O; and / or does not contain Li2O; and / or does not contain La2O3; and / or does not contain Gd2O3; and / or does not contain Y2O3; and / or does not contain Yb2O3; and / or does not contain ZnO; and / or does not contain P2O5; and / or does not contain BaO; and / or does not contain SrO; and / or does not contain CaO; and / or does not contain MgO.

[0019] (9) The refractive index n of the optical glass according to any one of (1) to (4) d is 1.45 to 1.51, preferably 1.46 to 1.50, more preferably 1.47 to 1.49, and the Abbe number v d It is 66-74, preferably 68-72, and more preferably 69-71.

[0020] (10) The optical glass according to any one of (1) to (4), wherein the transmittance of the optical glass at 365 nm is τ 365nm98.0% or more, preferably 99.0% or more, more preferably 99.5% or more; and / or the transmittance attenuation performance Δτ of the ultraviolet radiation resistance at 365nm 365nm 1.0% or less, preferably 0.9% or less, more preferably 0.8% or less; and / or the transmittance attenuation performance Δτ of the ultraviolet radiation resistance at 405nm 405nm 0.5% or less, preferably 0.3% or less, more preferably 0.2% or less; and / or the bubble degree is A grade or above, preferably A0 grade or above, more preferably A 00 and / or the stripe degree is C or above, preferably B or above; and / or the weather resistance CR is 2 or more, preferably 1; and / or the transition temperature T g 490°C or less, preferably 480°C or less, more preferably 475°C or less; and / or abrasion degree F A is 60 to 90, preferably 65 to 85, more preferably 70 to 80; and / or density ρ is 2.70 g / cm 3 Below, preferably 2.60g / cm 3 Below, more preferably 2.50g / cm 3 and / or refractive index batch stability of -15×10 -5 ~+15×10 -5 , preferably -10×10 -5 ~+10×10 -5 , more preferably -5×10 -5 ~+5×10 -5 , more preferably -2×10 -5 ~+2×10 -5 .

[0021] (11) A glass preform made of the optical glass described in any one of (1) to (10).

[0022] (12) An optical element, made of the optical glass described in any one of (1) to (10), or made of the glass preform described in (11).

[0023] (13) An optical instrument comprising the optical glass described in any one of (1) to (10) and / or the optical element described in (12).

[0024] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has a desired refractive index and Abbe number as well as a relatively low transition temperature and density. DETAILED DESCRIPTION

[0025] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.

[0026] Radiation-resistant optical glass with a refractive index of 1.45 to 1.51 and an Abbe number of 66 to 74 is a key material for the exposure lens of a lithography device, and its precision determines the precision level of the lens of the lithography device. Optical elements made of ordinary optical glass will have a significant decrease in transmittance and a change in refractive index under long-term irradiation in the ultraviolet band (355 to 430 nm), which is fatal to various types of lithography equipment working in the ultraviolet band. As chip manufacturing technology and advanced packaging technology develop towards lower line width and higher efficiency, lithography equipment working in this band needs to have higher resolution, higher light flux and larger exposure area. Correspondingly, the optical materials working on such lithography equipment are required to have a larger caliber, better radiation resistance, transmittance and optical uniformity. The main problem of this type of optical material in the prior art is that the ultraviolet radiation resistance is poor, and the transmittance attenuation can reach 5% under the verification conditions of the lithography equipment. At the same time, the 365nm transmittance of this type of material is low, which is difficult to meet the requirements of high-precision lithography equipment. In some embodiments, the transmittance of the optical glass of the present invention at 365nm (τ 365nm ) is 98.0% or more, preferably 99.0% or more, more preferably 99.5% or more, and the transmittance at 365nm is resistant to ultraviolet radiation attenuation performance (Δτ 365nm ) is less than 1.0%, preferably less than 0.9%, more preferably less than 0.8%, and the transmittance at 405nm is resistant to ultraviolet radiation attenuation performance (Δτ 405nm ) is 0.5% or less, preferably 0.3% or less, and more preferably 0.2% or less. The optical glass of the present invention can also be used in the fields of chip manufacturing and advanced packaging.

[0027] [Optical glass]

[0028] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content of each component and the total content are all expressed in weight percentage (wt%). In the present invention, except for the F (fluorine) component, the other components are expressed as oxides, and the sum of the weight percentage of all oxide components in the glass and the weight percentage of the F component in the glass is 100%.

[0029] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0030] <Essential Components and Optional Components>

[0031] SiO2 is the main network forming body component of the glass of the present invention. If the content of SiO2 is less than 50%, the transmittance of the glass at 365nm is low, which is fatal to ultraviolet optical systems with long light path and high illumination requirements, such as photolithography machine lenses, exposure machine prisms, etc. Therefore, the lower limit of the content of SiO2 is 50%, preferably 52%, and more preferably 54%. If the content of SiO2 is higher than 70%, the refractive index of the glass is difficult to meet the design requirements. At the same time, the glass needs to be melted at a higher temperature. The higher melting temperature will cause the erosion of the crucible by the glass liquid to grow exponentially. The ion content of iron (Fe) ions, platinum (Pt) ions, etc., which have a strong absorption effect on the ultraviolet band, rises rapidly, which leads to a rapid decrease in ultraviolet light transmittance, especially the transmittance at 365nm. In addition, the excessively high content of SiO2 will also cause the high-temperature viscosity of the glass to be too large, and the optical uniformity, bubble degree and stripe degree are difficult to meet the design requirements. Therefore, the upper limit of the content of SiO2 is 70%, preferably 68%, and more preferably 64%.

[0032] An appropriate amount of B2O3 can increase the refractive index of glass, strengthen the structure of glass, and improve the glass's meltability and resistance to ultraviolet radiation. If the content of B2O3 is higher than 18%, the erosion of the crucible by the glass liquid increases rapidly, resulting in a rapid decrease in ultraviolet light transmittance. If the content of B2O3 is lower than 2%, the glass is difficult to melt. Therefore, the content of B2O3 is 2 to 18%, preferably 4 to 16%, and more preferably 8 to 14%.

[0033] Al2O3 can improve the compactness of the internal structure of glass, and increase the ultraviolet light transmittance and chemical stability of glass. However, if its content exceeds 5%, stones are easily formed inside the glass, and the internal quality of the glass deteriorates. Therefore, the content of Al2O3 is 0-5%, preferably 0.1-3%, and more preferably 0.2-2%.

[0034] ZrO2 can improve the resistance of glass to devitrification, improve the chemical stability and mechanical properties of glass, reduce the corrosion of crucible materials during melting, and increase the ultraviolet transmittance of glass. If its content is too high, the melting difficulty of glass increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. Therefore, the content of ZrO2 in the present invention is 0-3%, preferably 0-2%, and more preferably 0-1%.

[0035] K2O improves the thermal stability and solubility of glass, reduces the transition temperature, reduces the high temperature viscosity of glass, provides free oxygen to strengthen the network structure of glass, and thus improves the ultraviolet light transmittance of glass. However, if its content is too high, the devitrification resistance and chemical stability of glass will decrease. Therefore, the content of K2O in the present invention is 10-30%, preferably 12-27%, and more preferably 13-25%.

[0036] Na2O can improve the solubility of glass and reduce the liquidus temperature of glass, but when its content is too high, it will accelerate the deterioration of the anti-crystallization performance of glass, and at the same time, it will prolong the time for glass to change from liquid to solid during cooling and forming, creating conditions for crystallization. Therefore, the content of Na2O in the present invention is 0-7%, preferably 0-5%, and more preferably 0-3%. In some embodiments, it is further preferred that Na2O is not contained.

[0037] Li2O can effectively reduce the transition temperature of glass, but optical glass is usually melted using platinum or platinum alloy vessels. During the high-temperature melting process, Li in the glass component easily corrodes the platinum or platinum alloy vessels, resulting in more platinum-containing foreign matter in the finished glass, resulting in a decrease in the ultraviolet light transmittance of the glass. Therefore, the content of Li2O in the present invention is 0-5%, preferably 0-4%, and more preferably 0-3%. In some embodiments, it is further preferred that Li2O is not contained.

[0038] In some embodiments, the ratio (Li2O+Na2O+K2O) / B2O3 between the total content of Li2O, Na2O and K2O Li2O+Na2O+K2O and the content of B2O3 is controlled within the range of 0.7 to 6.0, which can improve the ultraviolet light transmittance and refractive index batch stability of the glass. For photolithography equipment, refractive index batch stability is very important. Therefore, preferably (Li2O+Na2O+K2O) / B2O3 is 0.7 to 6.0, more preferably (Li2O+Na2O+K2O) / B2O3 is 0.8 to 5.0, further preferably (Li2O+Na2O+K2O) / B2O3 is 1.0 to 3.0, and further preferably (Li2O+Na2O+K2O) / B2O3 is 1.5 to 2.0.

[0039] In some embodiments, the ratio of the total content of Li2O, Na2O and K2O Li2O+Na2O+K2O to the content of SiO2 (Li2O+Na2O+K2O) / SiO2 is controlled within the range of 0.15 to 0.8, which can inhibit the volatilization of F in the glass, improve the batch stability of the refractive index of the glass, and reduce the transition temperature of the glass. Therefore, it is preferred that (Li2O+Na2O+K2O) / SiO2 is 0.15 to 0.8, and it is more preferred that (Li2O+Na2O+K2O) / SiO2 is 0.18 to 0.7. Furthermore, by controlling (Li2O+Na2O+K2O) / SiO2 within the range of 0.2 to 0.6, the abrasiveness, high temperature viscosity and weather resistance of the glass can be further optimized to a suitable range. Therefore, it is further preferred that (Li2O+Na2O+K2O) / SiO2 is 0.2 to 0.6, and it is further preferred that (Li2O+Na2O+K2O) / SiO2 is 0.2 to 0.45.

[0040] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3) is a component that can improve the refractive index and chemical stability of glass. By controlling the content of Ln2O3 to less than 5%, it is possible to prevent the devitrification resistance of glass from decreasing and prevent the refractive index and Abbe number of glass from exceeding the design requirements. Therefore, the content of Ln2O3 is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that La2O3 is not contained; and / or Gd2O3 is not contained; and / or Y2O3 is not contained; and / or Yb2O3 is not contained.

[0041] Nb2O5, TiO2, Bi2O3, Ta2O5, and WO3 are high-refractive and high-dispersion oxides, which can improve the anti-ultraviolet radiation performance of glass in glass, and can also improve the refractive index and dispersion of glass. However, when the content of the above oxides is high, the ultraviolet light transmittance of the glass will be reduced. Therefore, the content of Nb2O5 in the present invention is 0-2%, preferably 0-1%, and more preferably 0-0.8%. The content of TiO2 is 0-2%, preferably 0-1%, and more preferably 0-0.8%. The content of Bi2O3 is 0-2%, preferably 0-1%, and more preferably 0-0.5%. The content of WO3 is 0-2%, preferably 0-1%, and more preferably 0-0.5%. The content of Ta2O5 is limited to 0-3%, preferably 0-2%, and more preferably 0-1%.

[0042] In some embodiments, the ratio of the total content of Nb2O5, TiO2, Bi2O3, Ta2O5, and WO3 (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) to the content of B2O3 (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is controlled within a range greater than 0 but less than or equal to 0.8, which can improve the anti-ultraviolet radiation performance of the glass while preventing the reduction of the ultraviolet light transmittance of the glass, and optimize the bubble degree and refractive index batch stability of the glass. Therefore, it is preferred

[0043] (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is greater than 0 but less than or equal to 0.8, preferably

[0044] (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01~0.5, and it is further preferred that (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01~0.3, and it is further preferred that (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.02~0.2.

[0045] In some embodiments, the ratio (Nb2O5+TiO2) / Al2O3 between the total content of Nb2O5 and TiO2, Nb2O5+TiO2 and the content of Al2O3, is controlled to be below 2.0, which can improve the anti-ultraviolet radiation performance of the glass while preventing the density of the glass from increasing. Therefore, it is preferred that (Nb2O5+TiO2) / Al2O3 is below 2.0, and it is more preferred that (Nb2O5+TiO2) / Al2O3 is 0.01 to 1.5. Furthermore, by controlling (Nb2O5+TiO2) / Al2O3 within the range of 0.05 to 1.0, the abrasion and striae of the glass can be further optimized. Therefore, it is further preferred that (Nb2O5+TiO2) / Al2O3 is 0.05 to 1.0, and it is further preferred that (Nb2O5+TiO2) / Al2O3 is 0.1 to 0.5.

[0046] Alkaline earth metal oxide RO (RO is one or more of BaO, SrO, CaO, MgO) can adjust the optical constants and high temperature viscosity of the glass, but a high content of RO will lead to a decrease in the ultraviolet light transmittance and chemical stability of the glass. Therefore, the content of RO is 0-8%, preferably 0-5%, and more preferably 0-2%. In some embodiments, it is further preferred that BaO is not contained; and / or SrO is not contained; and / or CaO is not contained; and / or MgO is not contained.

[0047] ZnO can strengthen the network structure of glass, improve the refractive index and ultraviolet transmittance of glass. If the content of ZnO is too high, the phase separation tendency of glass increases, the ultraviolet transmittance decreases, and the stripe degree deteriorates. Therefore, the content of ZnO is 0-5%, preferably 0-2%, and more preferably less than 1%. In some embodiments, it is further preferred that ZnO is not contained.

[0048] P2O5 can reduce the melting temperature of glass raw materials and improve the ultraviolet transmittance of glass, but when its content is high, the anti-crystallization performance and chemical stability of glass deteriorate. Therefore, the content of P2O5 is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that P2O5 is not contained.

[0049] In the present invention, by containing 0-1% of one or more components of Sb2O3, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved, and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.2%. Since the component types and contents of the optical glass of the present invention are reasonably designed and its bubble degree is excellent, it is further preferred that no clarifier is contained in some embodiments. When the content of Sb2O3 exceeds 1%, the glass tends to have reduced clarification performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the forming mold. Therefore, the present invention preferably contains 0-1% of Sb2O3, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain Sb2O3. SnO2 can also be used as a clarifier, but when its content exceeds 1%, the tendency of glass coloring increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency to devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably no SnO2. The function and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably no CeO2.

[0050] F (fluorine) can reduce the transition temperature of glass, improve the ultraviolet light transmittance and ultraviolet radiation resistance of glass. If the F content is too high, it will volatilize greatly during the glass melting process, causing fluctuations in the glass refractive index and intrinsic quality (striation, bubble degree), and the optical uniformity of the glass will be difficult to meet the design requirements. It will also harm the production environment and the health of operators. Therefore, the F content is greater than 3% but less than or equal to 20%, preferably 5-16%, and more preferably 6-12%.

[0051] In some embodiments, the ratio F / B2O3 between the content of F and the content of B2O3 is controlled within the range of 0.2 to 5.0, which can improve the ultraviolet light transmittance of the glass and prevent the ultraviolet radiation resistance from deteriorating. Therefore, it is preferred that F / B2O3 is 0.2 to 5.0, and it is more preferred that F / B2O3 is 0.3 to 2.0. Furthermore, controlling F / B2O3 within the range of 0.4 to 1.5 can further optimize the bubble degree and abrasion degree of the glass. Therefore, it is further preferred that F / B2O3 is 0.4 to 1.5, and it is further preferred that F / B2O3 is 0.5 to 0.9.

[0052] In some embodiments, the ratio of Al2O3 content to F content, Al2O3 / F, is controlled to be below 1.0, which can prevent the ultraviolet light transmittance and weather resistance of the glass from decreasing. Therefore, Al2O3 / F is preferably below 1.0, and Al2O3 / F is more preferably below 0.8. Furthermore, controlling Al2O3 / F within the range of 0.01 to 0.5 can further improve the striation degree of the glass. Therefore, Al2O3 / F is further preferably 0.01 to 0.5, and Al2O3 / F is further preferably 0.07 to 0.3.

[0053] In some embodiments, the ratio K2O / F between the content of K2O and the content of F is controlled within the range of 0.7 to 7.0, which is beneficial to improving the striation degree and UV resistance of the glass and improving the batch stability of the refractive index of the glass. Therefore, K2O / F is preferably 0.7 to 7.0, more preferably 1.0 to 5.0, further preferably 1.5 to 3.0, and further preferably 1.8 to 2.8.

[0054] In some embodiments, controlling the ratio of SiO2 / (K2O+F) between the content of SiO2 and the total content of K2O and F (K2O+F) in the range of 1.2 to 4.5 is beneficial for the glass to obtain a suitable abrasion degree and transition temperature. Therefore, preferably SiO2 / (K2O+F) is 1.2 to 4.5, and more preferably SiO2 / (K2O+F) is 1.3 to 3.5. Furthermore, controlling SiO2 / (K2O+F) in the range of 1.5 to 3.0 can further improve the bubble degree and ultraviolet light transmittance of the glass. Therefore, it is further preferred that SiO2 / (K2O+F) is 1.5 to 3.0, and it is further preferred that SiO2 / (K2O+F) is 1.7 to 2.5.

[0055] In some embodiments, the ratio of the total content of ZrO2, Nb2O5 and TiO2 ZrO2+Nb2O5+TiO2 to the content of F (ZrO2+Nb2O5+TiO2) / F is controlled within the range of 0.01 to 1.0, and the glass has excellent ultraviolet radiation resistance and a low transition temperature while also having a suitable abrasion degree. Therefore, preferably (ZrO2+Nb2O5+TiO2) / F is 0.01 to 1.0, more preferably (ZrO2+Nb2O5+TiO2) / F is 0.01 to 0.8, further preferably (ZrO2+Nb2O5+TiO2) / F is 0.02 to 0.6, and further preferably (ZrO2+Nb2O5+TiO2) / F is 0.03 to 0.4.

[0056] <Components that should not be contained>

[0057] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.

[0058] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.

[0059] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.

[0060] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0061] Next, the properties of the optical glass of the present invention will be described.

[0062] <Refractive Index and Abbe Number>

[0063] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.

[0064] In some embodiments, the refractive index (n d The lower limit of the refractive index (n) of the optical glass of the present invention is 1.45, preferably 1.46, and more preferably 1.47. d ) has an upper limit of 1.51, a preferred upper limit of 1.50, and a more preferred upper limit of 1.49.

[0065] In some embodiments, the Abbe number (ν d ) has a lower limit of 66, preferably 68, and more preferably 69. In some embodiments, the Abbe number (ν d ) has an upper limit of 74, a preferred upper limit of 72, and a more preferred upper limit of 71.

[0066] <365nm transmittance τ 365nm >

[0067] The ultraviolet light transmittance of the optical glass of the present invention is characterized by the transmittance at 365 nm. The transmittance at 365 nm (τ 365nm ) Tested according to the method specified in GB / T7962.12-2010, the thickness of the glass sample is 10mm.

[0068] In some embodiments, the transmittance (τ 365nm ) is 98.0% or more, preferably 99.0% or more, and more preferably 99.5% or more.

[0069] <UV radiation resistance>

[0070] The UV resistance of optical glass is measured by Δτ 365nm or Δτ 405nm Characterization, Δτ 365nm That is, the transmittance at 365nm is resistant to ultraviolet radiation attenuation, Δτ 405nm That is, the transmittance at 405nm is resistant to ultraviolet radiation attenuation, Δτ 365nm or Δτ 405nm The lower the value, the better the glass's resistance to ultraviolet radiation.

[0071] Δτ 365nm The test method is: test the original transmittance τ of the sample at 365nm according to the method specified in GB / T7962.12-2010 365nm-1 , and then irradiated with a high-pressure mercury lamp, the power density on the glass surface is 1W / cm2 After 2 hours of irradiation, the transmittance τ at 365nm was tested again according to the method specified in GB / T7962.12-2010. 365nm-2 , the difference between the two tests τ 365nm-1 -τ 365nm-2 That is the attenuation of glass at this wavelength, and the thickness of the glass sample is 10 mm.

[0072] In some embodiments, the transmittance attenuation resistance to ultraviolet radiation of the optical glass of the present invention at 365 nm (Δτ 365nm ) is 1.0% or less, preferably 0.9% or less, and more preferably 0.8% or less.

[0073] Δτ 405nm The test method is: test the original transmittance τ of the sample at 405nm according to the method specified in GB / T7962.12-2010 405nm-1 , and then irradiated with a high-pressure mercury lamp, the power density on the glass surface is 1W / cm 2 After 2 hours of irradiation, the transmittance τ at 405nm was tested again according to the method specified in GB / T7962.12-2010 405nm-2 , the difference between the two tests τ 405nm-1 -τ 405nm-2 That is the attenuation of glass at this wavelength, and the thickness of the glass sample is 10 mm.

[0074] In some embodiments, the transmittance attenuation resistance to ultraviolet radiation of the optical glass of the present invention at 405 nm (Δτ 405nm ) is 0.5% or less, preferably 0.3% or less, and more preferably 0.2% or less.

[0075] <Bubble Degree>

[0076] The bubble degree of optical glass is measured and graded according to the method specified in GB / T 7962.8-2010.

[0077] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.

[0078] <Striation Degree>

[0079] The test method for the streak degree of optical glass is as follows: Use a point light source and a lens to form a streak meter, compare it with the standard sample from the direction where the streaks are most easily seen, and divide it into four levels according to the provisions in Table 1.

[0080] Table 1. Stripe grading standards

[0081] level Streak degree A No visible streaks under specified testing conditions B There are fine and scattered streaks under specified conditions C Slightly parallel streaks under specified conditions D Rough parallel striations under specified conditions

[0082] In some embodiments, the striae of the optical glass of the present invention is C level or higher, preferably B level or higher.

[0083] <Weather resistance>

[0084] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 2:

[0085] Table 2. Weather resistance classification standards

[0086]

[0087] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.

[0088] <Transition Temperature>

[0089] Transition temperature of optical glass (T g ) The test shall be carried out in accordance with the method specified in GB / T7962.16-2010.

[0090] In some embodiments, the transition temperature (T g ) is 490°C or lower, preferably 480°C or lower, and more preferably 475°C or lower.

[0091] <Abrasion>

[0092] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:

[0093] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100

[0094] Where: V—volume wear of the sample being tested;

[0095] V0—Volume loss of standard sample;

[0096] W—mass wear loss of the sample being tested;

[0097] W0—standard sample mass wear;

[0098] ρ—density of the sample being tested;

[0099] ρ0—standard sample density.

[0100] In some embodiments, the abrasiveness (F A ) has a lower limit of 60, a preferred lower limit of 65, and a more preferred lower limit of 70.

[0101] In some embodiments, the abrasiveness (F A ) has an upper limit of 90, a preferred upper limit of 85, and a more preferred upper limit of 80.

[0102] <density>

[0103] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.

[0104] In some embodiments, the density (ρ) of the optical glass of the present invention is 2.70 g / cm 3 Below, preferably 2.60g / cm 3 Below, more preferably 2.50g / cm 3 the following.

[0105] <Refractive Index Batch Stability>

[0106] The refractive index batch stability test method of optical glass is as follows: using the same glass formula, manufacturing method and equipment, melting twice respectively, and after obtaining the two glasses, testing the refractive index n of the previous glass respectively according to the method specified in GB / T7962.1-2010. d前 and the refractive index n of the subsequent glass d后 , n d后 -n d前 That is the batch stability of the refractive index of the glass material.

[0107] In some embodiments, the refractive index batch stability of the optical glass of the present invention is -15×10 -5 ~+15×10 -5 , preferably -10×10 -5 ~+10×10 -5 , more preferably -5×10 -5 ~+5×10 -5 , more preferably -2×10 -5 ~+2×10 -5 .

[0108] [Method for producing optical glass]

[0109] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and conventional processes, using carbonates, nitrates, sulfates, phosphates, metaphosphates, hydroxides, oxides, fluorides, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as a platinum crucible, a quartz crucible, etc.) at 1200-1450° C. for melting, and after clarification, stirring and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0110] [Glass preforms and optical components]

[0111] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.

[0112] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.

[0113] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.

[0114] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.

[0115] [Optical instruments]

[0116] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, photolithography equipment, vehicle-mounted equipment and monitoring equipment.

[0117] Example

[0118] <Optical Glass Example>

[0119] In order to further clearly illustrate and describe the technical solutions of the present invention, the following non-limiting examples are provided.

[0120] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 3 to 5. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 3 to 5.

[0121] Table 3.

[0122]

[0123]

[0124]

[0125] Table 4.

[0126]

[0127]

[0128] Table 5.

[0129]

[0130]

[0131] <Glass Preform Example>

[0132] The glass obtained from optical glass examples 1 to 21 is used, for example, by grinding processing, or by molding methods such as re-hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0133] <Optical Element Embodiment>

[0134] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.

[0135] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0136] <Optical Instrument Embodiment>

[0137] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.

Claims

1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 50-70%; B2O3: 2-18%; K2O: 10-30%; F: 4.53-20%; Nb2O5: 0-2%; TiO2: 0-2%; Al2O3: 0.1-5%, among which SiO2 / (K2O+F) is 1.2-2.5, and (Nb2O5+TiO2) / Al2O3 is 0.1-0.

5.

2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: ZrO2: 0-3%; and / or Na2O: 0-7%; and / or Li2O: 0-5%; and / or Ln2O3: 0-5%; and / or WO3: 0-2%; and / or Ta2O5: 0-3%; and / or Bi2O3: 0-2%; and / or RO: 0-8%; and / or ZnO: 0-5%; and / or P2O5: 0-3%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, RO is one or more of BaO, SrO, CaO, and MgO, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

3. Optical glass, characterized in that: The components are expressed in weight percentage, including: SiO2: 50-70%; B2O3: 2-18%; K2O: 10-30%; F: 4.53-20%, wherein SiO2 / (K2O+F) is 1.2-2.5, (Nb2O5+TiO2) / Al2O3 is 0.1-0.5, and the refractive index of the optical glass is n d is 1.45~1.51, Abbe number v d 66~74, transition temperature T g The temperature is below 490℃ and the density is 2.70g / cm 3 the following.

4. The optical glass according to claim 3, characterized in that: Its components, expressed in weight percentage, also contain: Nb2O5: 0-2%; and / or TiO2: 0-2%; and / or ZrO2: 0-3%; and / or Al2O3: 0.1-5%; and / or Na2O: 0-7%; and / or Li2O: 0-5%; and / or Ln2O3: 0-5%; and / or WO3: 0-2%; and / or Ta2O5: 0-3%; and / or Bi2O3: 0~2%; and / or RO: 0~8%; and / or ZnO: 0~5%; and / or P2O5: 0~3%; and / or clarifier: 0~1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, RO is one or more of BaO, SrO, CaO, and MgO, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

5. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following five conditions: 1) F / B2O3 is 0.2 to 5.0; 2) Al2O3 / F is less than 1.0; 3) K2O / F is 0.7 to 7.0; 4) SiO2 / (K2O+F) is 1.3 to 2.5; 5)(ZrO2+Nb2O5+TiO2) / F is 0.01~1.

0.

6. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following five conditions: 1) F / B2O3 is 0.3-2.0; 2) Al2O3 / F is less than 0.8; 3) K2O / F is 1.0 to 5.0; 4) SiO2 / (K2O+F) is 1.5 to 2.5; 5)(ZrO2+Nb2O5+TiO2) / F is 0.01~0.

8.

7. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following five conditions: 1) F / B2O3 is 0.4 to 1.5; 2) Al2O3 / F is 0.01 to 0.5; 3) K2O / F is 1.5 to 3.0; 4) SiO2 / (K2O+F) is 1.7 to 2.5; 5)(ZrO2+Nb2O5+TiO2) / F is 0.02~0.

6.

8. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following four conditions: 1) F / B2O3 is 0.5 to 0.9; 2) Al2O3 / F is 0.07-0.3; 3) K2O / F is 1.8 to 2.8; 4)(ZrO2+Nb2O5+TiO2) / F is 0.03~0.

4.

9. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is greater than 0 but less than or equal to 0.8; and / or (Li2O+Na2O+K2O) / B2O3 is 0.7~6.0; and / or (Li2O+Na2O+K2O) / SiO2 is 0.15~0.

8.

10. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01-0.5; and / or (Li2O+Na2O+K2O) / B2O3 is 0.8-5.0; and / or (Li2O+Na2O+K2O) / SiO2 is 0.18-0.

7.

11. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01-0.3; and / or (Li2O+Na2O+K2O) / B2O3 is 1.0-3.0; and / or (Li2O+Na2O+K2O) / SiO2 is 0.2-0.

6.

12. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.02-0.2; and / or (Li2O+Na2O+K2O) / B2O3 is 1.5-2.0; and / or (Li2O+Na2O+K2O) / SiO2 is 0.2-0.

45.

13. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed in weight percentage, wherein: SiO2: 52-68%; and / or B2O3: 4-16%; and / or K2O: 12-27%; and / or Nb2O5: 0-1%; and / or TiO2: 0-1%; and / or ZrO2: 0-2%; and / or F: 5-16%; and / or Al2O3: 0.1-3%; and / or Na2O: 0-5%; and / or Li2O: 0-4%; and / or Ln2O3: 0-3%; and / or WO3: 0- 1%; and / or Ta2O5: 0-2%; and / or Bi2O3: 0-1%; and / or RO: 0-5%; and / or ZnO: 0-2%; and / or P2O5: 0-2%; and / or clarifier: 0-0.5%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, RO is one or more of BaO, SrO, CaO, and MgO, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

14. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 54-64%; and / or B2O3: 8-14%; and / or K2O: 13-25%; and / or Nb2O5: 0-0.8%; and / or TiO2: 0-0.8%; and / or ZrO2: 0-1%; and / or F: 6-12%; and / or Al2O3: 0.2-2%; and / or Na2O: 0-3%; and / or Li2O: 0-3%; and / or Ln2O3: 0-1%; and / or WO3: 0- 0.5%; and / or Ta2O5: 0-1%; and / or Bi2O3: 0-0.5%; and / or RO: 0-2%; and / or ZnO: less than 1%; and / or P2O5: 0-1%; and / or clarifier: 0-0.2%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, RO is one or more of BaO, SrO, CaO, and MgO, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

15. The optical glass according to any one of claims 1 to 4, characterized in that: Its components do not contain Na2O; and / or do not contain Li2O; and / or do not contain La2O3; and / or do not contain Gd2O3; and / or do not contain Y2O3; and / or do not contain Yb2O3; and / or do not contain ZnO; and / or do not contain P2O5; and / or do not contain BaO; and / or do not contain SrO; and / or do not contain CaO; and / or do not contain MgO.

16. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.45~1.51; Abbe number v d It is 66 to 74.

17. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.46~1.50; Abbe number v d It is 68 to 72.

18. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.47~1.49; Abbe number v d It is 69 to 71.

19. The optical glass according to any one of claims 1 to 4, characterized in that: The transmittance of the optical glass at 365nm τ 365nm 98.0% or more; and / or the transmittance at 365nm UV radiation resistance attenuation performance Δτ 365nm Less than 1.0%; and / or transmittance at 405nm UV radiation attenuation performance Δτ 405nm 0.5% or less; and / or the bubble degree is A grade or above; and / or the streak degree is C grade or above; and / or the weather resistance CR is 2 or above; and / or the transition temperature T g 490℃ or less; and / or wear degree F A is 60 to 90; and / or density ρ is 2.70 g / cm 3 and / or refractive index batch stability of -15×10 -5 ~+15×10 -5 .

20. The optical glass according to any one of claims 1 to 4, characterized in that: The transmittance of the optical glass at 365nm τ 365nm 99.0% or more; and / or the transmittance at 365nm UV radiation resistance attenuation performance Δτ 365nm 0.9% or less; and / or the transmittance at 405nm UV radiation attenuation performance Δτ 405nm 0.3% or less; and / or the bubble degree is A0 or above; and / or the stripe degree is B or above; and / or the weather resistance CR is Class 1; and / or the transition temperature T g 480℃ or less; and / or wear degree F A is 65 to 85; and / or density ρ is 2.60 g / cm 3 and / or refractive index batch stability is -10×10 -5 ~+10×10 -5 .

21. The optical glass according to any one of claims 1 to 4, characterized in that: The transmittance of the optical glass at 365nm τ 365nm 99.5% or more; and / or the transmittance at 365nm UV radiation resistance attenuation performance Δτ 365nm 0.8% or less; and / or the transmittance at 405nm is Δτ resistant to ultraviolet radiation attenuation 405nm 0.2% or less; and / or the bubble degree is A 00 level; and / or transition temperature T g 475℃ or less; and / or wear degree F A is 70 to 80; and / or density ρ is 2.50 g / cm 3 and / or refractive index batch stability of -5×10 -5 ~+5×10 -5 .

22. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index batch stability of the optical glass is -2×10 -5 ~+2×10 -5 .

23. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 22.

24. An optical element, characterized in that It is made of the optical glass described in any one of claims 1 to 22, or is made of the glass preform described in claim 23.

25. An optical instrument, characterized in that Containing the optical glass according to any one of claims 1 to 22, and / or containing the optical element according to claim 24.

Citation Information

Patent Citations

  • Phosphate optical glass

    CN101300202A

  • Optical glass and optical element

    CN108529874A

  • Optical glass

    CN106116143A